Analysis and optimisation of different two-stage transcritical carbon dioxide cycles for heating applications. (October 2016) - Pitarch, M.; Navarro-Peris, E.; Gonzalvez, J.; Corberan, J.M.
Highlights: Analysis of several CO2 transcritical compression cycles to produce water at 80 °C. The evaluation has been done depending on the evaporation temperature. Optimisation of the intermediate conditions that maximise COP in that kind of cycles. Evaluation of possible strategies to reduce compressor discharge temperature in transcritical cycles. Abstract: Increased interest in the environmental impact of refrigeration technology is leading toward design solutions aimed at improving the energy efficiency and use of eco-friendly refrigerants with low GWP. The aim of this paper is to theoretically analyse R744 air to water heat pump cycles for heating applications up to 80 °C. This work studies the following cycle configurations: two-stage with injection (with and without intermediated cooling between compressors) and a single-stage circuit coupled with an auxiliary circuit. Internal heat transfer among the different streams of refrigerant is included, and the cycles have been optimised with regards to COP in terms of the intermediate conditions and gas cooler pressure. Finally, these cycles have been compared and analysed among each other and with a subcritical injection cycle working with R134a and a single-stage R744 cycle. The improved cycle with R744 can represent a global improvement of 15% in terms of COP.